Intraguild interactions between two biological control agents in citrus fruit: implications for biological control of medfly. (19th February 2018) - Tormos, J.; Beitia, F.; Asís, J.D.; de Pedro, L.
Abstract: The parasitoid wasp Spalangia cameroni and the predatory beetle Pseudoophonus rufipes have long been studied for use as biological control agents against the Mediterranean fruit fly Ceratitis capitata, particularly in citrus fruit orchards. Nevertheless, these two species of natural enemies, when competing for a common resource, may experience intraguild predation (IGP) interactions. These possible interactions, affecting parasitism and predation, have been evaluated in the present work, under laboratory conditions, through potential changes in functional response. Regarding host/prey density, both natural enemies, when acting alone, showed a type II functional response. Nevertheless, due to IGP, S. cameroni, in the presence of P. rufipes, showed a higher fertility rate and a type III functional response. The parasitism behaviour of S. cameroni was affected by the presence of the predator, reducing the host handling time. Conversely, the parasitism rate of S. cameroni did not vary in the presence of P. rufipes but the degree of superparasitism decreased and led to an increased fertility rate and an increasingly female‐biased sex ratio. Meanwhile, the predatory efficiency of P. rufipes was not affected by the presence of S. cameroni but discrimination between parasitised and unparasitised pupae of C. capitata, with a preference for the latter, was reported for this predator species. Our results suggest that in biological control programmes, the use of only one of these species is recommended at low infestation levels, whilst at high densities of the pest, the combination of both natural enemies seems to be the most appropriate strategy. Abstract : Functional response curve fit by non‐linear least‐squares regression of fertilised Spalangia cameroni females infesting Ceratitis capitata pupae and sharing the experimental unit with Pseudoophonus rufipes adults predating C. capitata pupae (type III). Host density: 2, 4, 6, 8, 10, 14, 20, 30 or 40 pupae per fertilised S. cameroni female (one or three) and P. rufipes adult (one or three) (both natural enemies exposed together in the same experimental unit) and day. For host densities above 40, values are shown in grey as they are an extrapolation beyond recorded data.